Pencegahan Komplikasi Hipertensi Dengan Pemberian Edukasi Kesehatan pada Majelis Talim Pengajian Masjid Al Jannah Mojosongo - Khayudin, Bayu Akbar; Sumardino, Sumardino (Journal of Health Innovation and Community Services, 2025)
Background Hypertension is a non-communicable disease that is a major health problem at both global and national levels. Its complications are very serious, such as coronary heart disease, kidney failure, stroke, and sudden death. Lack of public knowledge about the importance of controlling blood pressure is one of the causes of the high number of complications due to hypertension. Health education plays a crucial role in increasing public awareness and promoting behaviors that facilitate early prevention through adopting a healthy lifestyle, adhering to medication regimens, and engaging in routine blood pressure monitoring. Objective: to increase public knowledge and awareness about preventing hypertension complications through providing health education. Method: The method of health education uses interactive lectures, discussions, and the distribution of educational leaflets. Participants were the congregation of the Al Jannah Mojosongo mosque ta'lim assembly. Results: showed an increase in participants' knowledge about hypertension, its complications, and prevention efforts. Participants also stated that they were more motivated to adopt healthy lifestyle behaviors and have their blood pressure checked regularly. Conclusion: Providing health education has been proven effective in increasing public knowledge about preventing hypertension complications.